2021
DOI: 10.56093/ijans.v90i9.109324
|View full text |Cite
|
Sign up to set email alerts
|

Artificial insemination in pig, its status and future perspective in India: A review

Abstract: The pig production must be sustainable, efficient and competitive to minimize its impact on environment. There is argument to keep fewer breedable animals to produce more numbers of piglets. In India, pig rearing is still done on traditional manner with low productivity. Artificial insemination (AI) is the best reproductive technology available in the current scenario for enhancing the efficiency of pig production in a sustainable way. This in pig involves, collection of semen, processing in laboratory, packag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…The health status (Hodel et al, 2021) and frequency of use of rental boars may compromise semen quality, which would potentially reduce their reproductive efficiency (Am-in et al, 2010). It was previously reported that farmers uses the same boar for breeding purpose in a village for three to four years over few breedable sows (Kadirvel et al, 2013;Singh and Mollier, 2020). This leads to inbreeding which results in low productivity and reproductive efficiency.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The health status (Hodel et al, 2021) and frequency of use of rental boars may compromise semen quality, which would potentially reduce their reproductive efficiency (Am-in et al, 2010). It was previously reported that farmers uses the same boar for breeding purpose in a village for three to four years over few breedable sows (Kadirvel et al, 2013;Singh and Mollier, 2020). This leads to inbreeding which results in low productivity and reproductive efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…The semen doses used in the present study were collected from boars (Ghungroo × Hampshire) reared at the ICAR Nagaland Centre's Pig Research Farm. Semen from boars was collected using the gloved hand method (Singh and Mollier, 2020). Semen was transported in a thermos flask to the laboratory within 15 min of collection.…”
Section: Semen Collection and Processingmentioning
confidence: 99%
See 3 more Smart Citations